The Influence of Code Retrieval from the Web on Programmer’s Skills, Meth-odologies, and Coding Behaviors - Alfaroq O.M. Mohammed; Ziad A. Abdelnabi; Abdalmunam Abdalla (مجلة المختار للعلوم, 2021)
The development of software projects consists of several stages, such as analysis and design. It also requires a set of skills that the software developer can use to work on the project, such as specifying the requirements and writing code. Developers usually search for source code on the internet for remix and reuse in software production. This paper aims to investigate the influence and effect of code retrieved from the web on programmers’ views, decisions, and skills. A questionnaire instrument was designed and distributed to programmers for their feedback. As a result, we were able to address some points and achieved a better understanding of the interaction between programmers and the code from the web, especially the code from programming forums such as Stack Over Flow.